In pursuit of a lifelong learning society : a historical analysis of lifelong learning policy discourses from major international organizations - Lee, Moosung (Emerald Publishing Limited, 2025)
In Pursuit of a Lifelong Learning Society explores the policy discourses of lifelong learning articulated by three major international organisations - UNESCO, OECD, and the EU. Through comparative analysis, Moosung Lee explores how these organizations have shaped lifelong learning policies through their ideologies and interactions, bridging fields such as adult education, policy analysis, social policy, sociology, and comparative education. By tracing the historical evolution of these policies, chapters explore alternative discourses aimed at building a learning society and restoring the authenticity of lifelong learning. Key policy texts are analysed to provide real-world implications, highlighting the commonalities and differences in the organizations' discourses and their evolution. The book identifies distinctive features of each organization's policies, explores their historical development, and critically analyses their global educational implications. The comparative approach adopted throughout will interest policy researchers designing lifelong learning systems at local and national levels, as well as those studying global educational policy trends and their impacts. Researchers in global studies and international relations, particularly those focused on the role of international organizations in global governance, will also find it valuable.
Keywords: Continuing education -- Government policy.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books